Informatics and Technology in Clinical Care and Public Health - Hasman, Arie; Hasman, Arie; Househ, Mowafa S.; Zoulias, Emmanouil (SAGE Publications, 2022)
Data, informatics, and technology are now among the most important aspects inspiring health professionals and informaticians to improve healthcare for the benefit of patients. This book presents the proceedings of the 19th annual International Conference on Informatics, Management, and Technology in Healthcare (ICIMTH 2021), held as a virtual event due to COVID-19 pandemic restrictions on 16 and 17 October 2021 in Athens, Greece. The ICIMTH conferences are a series of scientific events which bring together scientists working in the field of biomedical and health informatics from around the world. The 2021 conference examined the field of biomedical and health informatics in a very broad framework, presenting the research and application outcomes of informatics from cell to populations, and including a number of technologies such as imaging, sensors and biomedical equipment, as well as management and organizational aspects, including legal and social issues and the setting of research priorities in health informatics. A significant number of the papers included here relate to the COVID-19 pandemic. Providing an insight into the latest developments in biomedical and health informatics, the book will be of interest to all those working in the field.